(untitled) (Journal of Global Arts Studies, 2025)
Background： With the deepening reform of the new college entrance examination, it is increasingly important to explore the artistic traits of "the beauty of number-shape combination" in analytic geometry and build a math teaching model integrating artistic perception and focusing on mathematical thinking infiltration. Objective： To explore its construction path: to guide teachers to integrate artistic perception for students’ mathematical thinking enhancement, inject artistic creativity into math classes, and offer references for "mathematical aesthetics"-related practices. Methods: Taking high school analytic geometry as the subject, it sorts out "the beauty of number-shape combination" elements in 5-year new college entrance exam analytic geometry questions; via tests, interviews and questionnaires, it surveys Luoyang/Jiyuan (Henan) students on their perception of this beauty and analytic geometry mastery, then refines a better model with cases. Results: Teachers should hierarchically infiltrate mathematical thinking based on curve beauty, symmetry and other artistic traits for students of different levels; guide students from "perceiving graphic beauty" to "understanding mathematical beauty" in different stages, and master flexible application of mathematical thinking. Conclusion: The model (with "the beauty of number-shape combination" as artistic link and mathematical thinking as core) needs two-way empowerment: improving teachers’ professional abilities and students’ dual development of math literacy + artistic perception. Teachers’ mathematical thinking cognition, infiltration teaching ability and artistic material integration ability are three key supports, offering a practical paradigm for teaching reconstruction.